Analisa Tulangan pada Blok Angkur Jembatan Gantung dengan menggunakan Ansys - Indra Jhon Fischer; Johannes Tarigan; Emma Patricia Bangun (CV. Syntax Corporation Indonesia, 2022)
The strength of the anchor block structure in the suspension bridge is very dependent on its weight to be able to bear the tensile load of the backstay cable. Therefore, it is necessary to have dimensions large enough to withstand the tensile force. Concrete has good compressive strength but does not have good tensile strength, the tensile strength of concrete is only about 10%-15% of its compressive strength. Therefore, in planning anchor blocks, anchor blocks are needed making of steel that has high yield and fracture stresses and is planted in anchor concrete blocks to withstand the force before the tensile stresses are transferred to the concrete blocks. In this paper, steel H 300.300.10.15 is used as steel anchors embedded in concrete blocks. The purpose of this study was to obtain the stress value that occurs in the anchor block using the Ansys assistance program, obtain the appropriate reinforcement distance in the maximum tensile area (critical area), and obtain a graphic description of the influence of the anchor structure geometry due to the load from the backstay cable. This research was conducted using a numerical study using the SAP 2000 assistance program to calculate the forces in the entire suspension bridge structure, then using the Ansys analysis assistance program to obtain the tensile stress that occurs in the anchor block which is also modeled in Ansys with boundary conditions that are close to the existing conditions in the field. The results of Ansys analysis show that the maximum tensile stress in H profile steel 300.300.10.15 is 73.27 MPa and the maximum tensile stress in concrete is 1.26 MPa. The value of 1.26 MPa is still within a safe limit because the tensile stress is still below the allowable tensile stress for the concrete of 2.23 MPa. From the results of empirical analysis, the maximum reinforcement space in the critical area is 150 mm, and in the non-critical area, it is 250 mm.